Obstructive sleep apnea phenotypes eligible for pharmacological treatment - Bruyneel, Marie (Frontiers in Sleep, 2023)
Obstructive sleep apnea (OSA) is a common disorder. Its prevalence is increasing worldwide, partially due to increasing rates of obesity, and OSA has a well-documented impact on physical health (increased risk of cardiovascular and metabolic disorders) and mental health, as well as major socioeconomic implications. Although continuous positive airway pressure treatment (CPAP) remains the primary therapeutic intervention for moderate to severe OSA, other treatment strategies such as weight loss, positional therapy, mandibular advancement devices (MAD), surgical treatment, myofunctional therapy of upper airways (UA) muscles and hypoglossal nerve stimulation are increasingly used. Recently, several trials have demonstrated the clinical potential for various pharmacological treatments that aim to improve UA muscle dysfunction, loop gain, or excessive daytime sleepiness. In line with the highly heterogeneous clinical picture of OSA, recent identification of different clinical phenotypes has been documented. Comorbidities, incident cardiovascular risk, and response to CPAP may vary significantly among phenotypes. With this in mind, the purpose of this review is to summarize the data on OSA phenotypes that may respond to pharmacological approaches.